1998
DOI: 10.1074/jbc.273.26.16521
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of de NovoCeramide Biosynthesis in Tumor Necrosis Factor-α/Cycloheximide-induced Cerebral Endothelial Cell Death

Abstract: Cytokines, including tumor necrosis factor-␣ (TNF-␣), may elicit cytotoxic response through the sphingomyelin-ceramide signal transduction pathway by activation of sphingomyelinases and the subsequent release of ceramide: the universal lipid second messenger. Treatment of bovine cerebral endothelial cells (BCECs) with TNF-␣ for 16 h followed by cycloheximide (CHX) for 6 h resulted in an increase in ceramide accumulation, DNA fragmentation, and cell death. Application of a cell permeable ceramide analogue C 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
142
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 42 publications
(47 reference statements)
6
142
1
Order By: Relevance
“…Previously, it was suggested that heat stress signaling could also be mediated via de novo synthesis of sphingoid bases (9,10). Also in mammalian cells, de novo synthesis of ceramide has been suggested to be important in apoptosis (32)(33)(34)(35). Despite our data, we cannot rule out the possibility that the generation of PHS by hydrolysis of other sphingolipids such as PHC, inositol phosphoceramide, and others may also play a role in growth inhibition.…”
Section: Discussioncontrasting
confidence: 50%
“…Previously, it was suggested that heat stress signaling could also be mediated via de novo synthesis of sphingoid bases (9,10). Also in mammalian cells, de novo synthesis of ceramide has been suggested to be important in apoptosis (32)(33)(34)(35). Despite our data, we cannot rule out the possibility that the generation of PHS by hydrolysis of other sphingolipids such as PHC, inositol phosphoceramide, and others may also play a role in growth inhibition.…”
Section: Discussioncontrasting
confidence: 50%
“…TNF-␣ has been shown to elevate cellular ceramide by both stimulating de novo ceramide synthesis (82,83) and increasing ceramide generation from sphingomyelin hydrolysis (84). In this study, we found an age-associated elevation in both TNF-␣ and ceramide and, thus, one might argue that the higher ceramide levels are due to elevated TNF-␣ production with aging.…”
Section: Discussionsupporting
confidence: 45%
“…Therefore, TNF-α, one of many cytokines, holds a very central role in arteriosclerosis. A direct relationship has been identified between TNF-α and ceramide, in which TNF-α has been shown to be responsible for increases in intracellular (vascular endothelial cells) ceramide content [24,25]. Zhang et al found that TNF-α could trigger SMase and augment superoxide anion generation in endothelial cells.…”
Section: Tumor Necrosis Factor-α and Ceramidementioning
confidence: 99%
“…Zhang et al found that TNF-α could trigger SMase and augment superoxide anion generation in endothelial cells. Furthermore, they found that, indeed, TNF-α caused a rapid increase of superoxide free radical within 2 minutes, but the effect was not sustained and dissipated after 60 minutes [24,25]. TNF-α can stimulate ceramide formation via the activation of both neutral and acid SMases, accompanied by ROS such as superoxide anion production [26].…”
Section: Tumor Necrosis Factor-α and Ceramidementioning
confidence: 99%